Step
*
1
of Lemma
ranked-eo-eq-E
1. L : Top
2. rk : Top
3. a1 : Top
4. a2 : ℤ
5. b1 : Top
6. b2 : ℤ
⊢ a1 = b1 ∧b (¬ba2 <z b2) ∧b (¬bb2 <z a2) ~ a1 = b1 ∧b (a2 =z b2)
BY
{ (EqCD THEN Auto) }
Latex:
Latex:
1.  L  :  Top
2.  rk  :  Top
3.  a1  :  Top
4.  a2  :  \mBbbZ{}
5.  b1  :  Top
6.  b2  :  \mBbbZ{}
\mvdash{}  a1  =  b1  \mwedge{}\msubb{}  (\mneg{}\msubb{}a2  <z  b2)  \mwedge{}\msubb{}  (\mneg{}\msubb{}b2  <z  a2)  \msim{}  a1  =  b1  \mwedge{}\msubb{}  (a2  =\msubz{}  b2)
By
Latex:
(EqCD  THEN  Auto)
Home
Index